Immune Response to Gluten in Adult Coeliac Disease. Issue 5650 (19th April 1969) - Housley, J.; Asquith, P.; Cooke, W. T.
Abstract : Cultures of mesenteric node lymphocytes obtained from two adult coeliac disease patients were stimulated by gluten fraction III. No stimulation was observed in cultures of axillary node lymphocytes from one of these patients, of mesenteric node lymphocytes from the two patients with other diseases or of peripheral blood lymphocytes from adult coeliacs and normal subjects. Peripheral blood lymphocytes of two of the six adult coeliac patients responded poorly to phytohaemagglutin alone, but this was probably owing to technical factors. In a further six adult coeliacs skin tests to gluten fraction III were negative. It is suggested that delayed hypersensitivity to gluten is likely to have a secondary pathogenic role in adult coeliac disease.